2021
DOI: 10.17159/2310-3833/2021/vol51n1a6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of parent-administered infant massage on the developmental outcomes of premature infants

Abstract: Introduction: Prematurely born infants often have developmental delays in multiple areas when compared to infants born at term. Neurodevelopmental supportive care techniques such as Kangaroo Mother Care or infant massage have the potential to affect the infant's developmental outcome. Evidence supports the benefits of parent-administered infant massage in terms of the premature infants' growth, weight gain and length of hospitalisation. However, the effect of infant massage on other aspects of development has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Two of these studies ( 23 , 24 ) used Neonatal Behavior Assessment Scores (NBAS) and Test of Infant Motor Performance (TIMP) to assess the motor function of preterm infants before and after receiving the intervention. One study used the Bayley Scales of Infant and Toddler Development-Third Edition (BSID-III) ( 25 ), while the other study ( 39 ) used direct observation of infant limb and trunk movements to assess whether massage therapy improved motor function in preterm infants. Massage therapy had no statistically significant effect on improving the motor function in preterm infants, according to the four studies that evaluated its effectiveness on motor function in preterm infants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two of these studies ( 23 , 24 ) used Neonatal Behavior Assessment Scores (NBAS) and Test of Infant Motor Performance (TIMP) to assess the motor function of preterm infants before and after receiving the intervention. One study used the Bayley Scales of Infant and Toddler Development-Third Edition (BSID-III) ( 25 ), while the other study ( 39 ) used direct observation of infant limb and trunk movements to assess whether massage therapy improved motor function in preterm infants. Massage therapy had no statistically significant effect on improving the motor function in preterm infants, according to the four studies that evaluated its effectiveness on motor function in preterm infants.…”
Section: Resultsmentioning
confidence: 99%
“…All 15 included studies used massage therapy as an intervention for preterm infants. Twelve of these studies used the Field protocol ( 21 – 23 , 25 28 , 37 41 ), which consists of massage therapy starting at a corrected gestational age of 35 weeks for five consecutive days, one hour after feeding, three times a day for 15 min. Each treatment was divided into 5 min of tactile stimulation, followed by 5 min of kinesthetic stimulation, and then another 5 min of tactile stimulation ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, pediatric massage is extensively used in neonatal intensive care units (NICUs) and has consistently been shown to produce beneficial effects in premature infants, most notably for promoting growth and health and earlier discharge from NICUs (see Field, 2002 , 2019 ; Badr et al, 2015 ; Niemi, 2017 ; Liao et al, 2021 ). Additionally, studies have reported positive results of massage on immune system ( Karamian et al, 2022 ) as well as on cognitive and visual function and visuomotor integration ( Guzzetta et al, 2009 ; Fontana et al, 2020 ; Campbell and Jacobs, 2021 ) and on the strength of mother–infant bonding ( Shoghi et al, 2018 ). Currently, many different forms of pediatric massage have been used across cultures.…”
Section: Evidence For Importance Of Touch For Brain and Behavioral De...mentioning
confidence: 99%